การศึกษาการบริหารครูชาวต่างชาติของโรงเรียนเอกชนสองภาษาในกรุงเทพมหานคร - จันแดง มัณฑลิน; สุเมตติกุล ปิยพงษ์ (An Online Journal of Education, 2018)
Abstract5 This descriptive research aimed at studying the current and desirable states, and the priority needs for management of foreign teachers in private bilingual school within the Bangkok Metropolis. The population of this research were private bilingual schools principles with a sample size of 59. A questionnaire with the rating scale was used to collect data at a return rate of 100 percent. A descriptive statistical analysis including frequency, percentage, mean, standard deviation and qualitative data. A content analysis and Priority Needs Index (PNI modified) were used to prioritize the requirement of the management of private bilingual schools. The results show the desirable state of management of foreign teachers investigated at a high level when sorted with a PNI modified. They were 1) The training of language and Thai culture 2) The contracting of the performance employment 3) The competency of English language. Therefore, they were considered weaknesses and should be further developed. The other 5 aspects were considered strengths and should be encouraged. They were 1) The skill of speaking and using English language 2) The training and development 3) The partnership and relationship 4) The degree obtained 5) The Educational Psychology.